Switching from manual procurement to E-procurement at Permodalan Nasional Berhad / Mohd Shahreel Sharun - Sharun, Mohd Shahreel (Faculty of Business and Management, 2009)
Supply Chain Management consists of firm collaborating to leverage strategic positioning and to improve operating efficiency. Due to this, firm need to improve their supply chain in many aspects. One of the ways to improve their supply chain is through effective procurement activities. Procurement activities have been evolved into a new era of Internet Technology that uses Internet or World Wide Web as a medium to obtain goods and services from a supplier. The researcher believes that enormous cost savings and efficiencies can be achieved through the utilization of e-procurement, a component of the B2B model. Permodalan Nasional Berhad also is trying to develop e-procurement in their procurement activities and switch from manual procurement to e-procurement. This research analyzes some challenges that will faced by the organization. Therefore, there are few suggestions by the researcher in order to increase the effectiveness of the e-procurement.